2021
DOI: 10.4103/injms.injms_149_20
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescribing Trends and Safety Profile in Pediatric Care

Abstract: Background: Globally, pharmacovigilance, rationality of drug prescription studies, and adverse drug reaction (ADR) in children affected with ailments are an understudied topic. Children are a vulnerable age group and reports suggest that over 10% of hospitalized have adverse reactions to therapy and up to 2.9% of all hospital admissions are the consequence of ADRs. In lieu of these observations, the present study was undertaken in a tertiary care hospital to ascertain the bad prescribing habits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Sindhu and Ahmed 4 also found that the most common antimicrobials prescribed in PICU were third-generation cephalosporins, namely ceftriaxone, and suggested that antibiotic overuse was likely due to paucity in support for decision-making. Another study by Fathima et al 5 found that antipyretics and antimicrobials were the most common drugs prescribed.…”
Section: Introductionmentioning
confidence: 99%
“…Sindhu and Ahmed 4 also found that the most common antimicrobials prescribed in PICU were third-generation cephalosporins, namely ceftriaxone, and suggested that antibiotic overuse was likely due to paucity in support for decision-making. Another study by Fathima et al 5 found that antipyretics and antimicrobials were the most common drugs prescribed.…”
Section: Introductionmentioning
confidence: 99%